Inisiasi Pelatihan Basic English for Tourism sebagai Upaya Peningkatan Kesiapan Komunikasi Masyarakat Desa Karangpring, Kecamatan Sukorambi - Meiga Rahmanita; Firda Diartika; Nodistya Septian Indrastana; Renata Kenanga Rinda; Titik Ismailia (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Karangpring Village, Sukorambi District, Jember Regency, has considerable natural and cultural tourism potential that continues to be developed. However, the local community's readiness to communicate in English as part of tourism services remains limited. This community service program aimed to describe the implementation of a Basic English for Tourism training program and examine its role in improving the community's communication readiness to support village tourism development. The training involved 12 participants representing the Youth Organization (Karang Taruna), Village-Owned Enterprise (BUMDes), village facilitators, and Micro, Small, and Medium Enterprises (MSMEs). The program was conducted through four stages: material presentation, guided practice, communication practice through role play, and evaluation. The training focused on giving directions, greeting visitors, and introducing oneself and the tourist destination by using local tourism attractions as learning contexts. The results showed that participants were highly engaged and gradually became able to use basic English expressions in simulated tourism service situations. Although many participants were initially hesitant and struggled to communicate, continuous guidance through role play helped improve their confidence and willingness to speak English. The evaluation results also indicated positive participant responses regarding the training materials, delivery, and overall benefits. Therefore, the Basic English for Tourism training can serve as an initial step in strengthening the communication capacity of local communities to support the development of Karangpring Village as a tourist destination.